UMPSA recognizes 109 lecturers in the Cendekia Bitara Awards Ceremony - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUANTAN, 15 September 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has proven its pride in having world-class researchers as it awards 109 individuals, comprising 101 Cendekia Bitara Awards (Anugerah Cendekia Bitara - ACB), six University e-Learning Awards (APU), and two University Academic Awards (AAU). These awards are dedicated to its academic community members who have shown excellence and expertise in the field of teaching and learning.